TINJAUAN PELAKSANAAN PENCEGAHAN CROSS CONTAMINATION BAHAN PANGAN DI DAPUR 18th THE TRANS LUXURY HOTEL BANDUNG - Senia Azka Aurora; Yayan Setiawan (JURNAL PARIWISATA VOKASI, 2021)
This study aims to determine the implementation of preventing cross contamination of foodstuffs in the 18th kitchen of The Trans Luxury Hotel Bandung. The type of research method chosen and used by the author is descriptive method. Data collection techniques were carried out by direct observation, distributing questionnaires, and studying literature. While the data analysis technique using a Likert scale. Based on the results of the study, it can be seen that in general the prevention of cross contamination of food ingredients in the 18th kitchen of The Trans Luxury Hotel Bandung is good, it's just that there are dimensions that need to be considered, such as: how to wash hands before preparing food, the cooks are still not good and to be further improved and think about the impact that will occur if you do not wash your hands before preparing food. The competence of front office employees at The Luxton Hotel Bandung can be classified as good, it's just that there are dimensions that need to be considered, namely the attitude dimension. Where an employee is said to be competent if the employee is based on knowledge, skills and work attitudes, so that his professionalism is still in doubt. Problems in research: 1) How is the cleanliness in the 18th kitchen of The Trans Luxury Hotel Bandung?. 2) How is the completeness of the equipment in the 18th kitchen of The Trans Luxury Hotel Bandung?. 3) How is the cook in the 18th kitchen of The Trans Luxury Hotel?. 4) Bandung in washing hands before preparing food? 5) How does the cook in the 18th The Trans LuxuryHotel Bandung kitchen wash their hands after touching raw food? 6) How to store raw and ready-to-eat food in the 18th kitchen of The Trans Luxury Hotel Bandung ?. 7) What is the number of food storage areas in the 18th The Trans Luxury Hotel's kitchen?8) How is the knowledge of cross-contamination by the cooks in the 18th The Trans Luxury Hotel Bandung's kitchen?